Are Changes to the Common Rule Necessary to Address Evolving Areas of Research? A Case Study Focusing on the Human Microbiome Project. Issue 2 (26th June 2013) - Hoffmann, Diane E.; Fortenberry, J. Dennis; Ravel, Jacques
<x xml:space="preserve">Abstract</x> This article examines ways in which research conducted under the Human Microbiome Project, an effort to establish a "reference catalogue" of the micro‐organisms present in the human body and determine how changes in those micro‐organisms affect health and disease, raise challenging issues for regulation of human subject research. The article focuses on issues related to subject selection and recruitment, group stigma, and informational risks, and explores whether: (1) the Common Rule or proposed changes to the Rule adequately address these issues and (2) the Common Rule is the most appropriate vehicle to provide regulatory oversight and guidance on these topics.